FAP and FAPI-PET/CT in malignant and non-malignant diseases: a perfect symbiosis? - Dendl, Katharina; Körber, Stefan A.; Kratochwil, Clemens; Cardinale, Jens; Finck, Rebecca; Dabir, Mardjan; Novruzov, Emil; Watabe, Tadashi; Kramer, Vasko; Choyke, Peter L.; Haberkorn, Uwe; Giesel, Frederik L. (Cancers, 2021)
A fibroblast activation protein (FAP) is an atypical type II transmembrane serine protease with both endopeptidase and post-proline dipeptidyl peptidase activity. FAP is overexpressed in cancer-associated fibroblasts (CAFs), which are found in most epithelial tumors. CAFs have been implicated in promoting tumor cell invasion, angiogenesis and growth and their presence correlates with a poor prognosis. However, FAP can generally be found during the remodeling of the extracellular matrix and therefore can be detected in wound healing and benign diseases. For instance, chronic inflammation, arthritis, fibrosis and ischemic heart tissue after a myocardial infarction are FAP-positive diseases. Therefore, quinoline-based FAP inhibitors (FAPIs) bind with a high affinity not only to tumors but also to a variety of benign pathologic processes. When these inhibitors are radiolabeled with positron emitting radioisotopes, they provide new diagnostic and prognostic tools as well as insights into the role of the microenvironment in a disease. In this respect, they deliver additional information beyond what is afforded by conventional FDG PET scans that typically report on glucose uptake. Thus, FAP ligands are considered to be highly promising novel tracers that offer a new diagnostic and theranostic potential in a variety of diseases.
Gesehen am 22.01.2022